Architecture under occupation: the development of public and residential structures in German–occupied Lithuania (1941–1944) - Vilkončius, Evaldas (Landscape Architecture and Art, 2025)
The German occupation of Lithuania, which lasted from 1941 to 1944, was a period that affected all areas of life, including architecture and construction. Thus, the aim of this paper is to present a short, yet dramatic and difficult period in the history of Lithuanian architecture – the development and transformation of public and residential structures amidst the German occupation. The research is based on the study of archival material, literature, and periodicals of that period, as well as recent works on this topic, while the text is supplemented with the design projects of public and residential structures. The article demonstrates that even under the conditions of the German occupation, there was still a strong emphasis on developing public and residential architecture in Lithuania, and the processes regarding the matter were quite actively taking place. As most of the planned structures were not realized at that time, the article assumes that architectural activity during that time can be identified only with the compilation of plans for the needed construction, the development of civil building projects, and theoretical discussions regarding the stylistic properties of Lithuanian architecture.